Disminución de la agudeza visual en paciente masculino de 33 años causada por cuerpo extraño orgánico en ojo derecho. - Avilés Morales, Gladys Carolina (2021)
The decrease in visual acuity can be caused by various factors affecting our vision, which can be caused by different causes, among the most frequent being the insertion of an organic foreign body. In other words, it is one of the main causes of partial or total vision loss and if not treated in time can cause severe damage to our vision. The objective of this study is to establish and specify the cause of the decrease in vision with the respective visual assessment tests, which includes visual acuity both at a distance (6m) and near (35-40 cm). When observing that the patient did not improve his visual acuity with refraction, he was referred to the ophthalmologist who determined that his problem was due to a decrease in distant visual acuity, foreign body sensation, blurred visión, ocular burning after ocular trauma with a metallic object which did not allowed the images to reach the retina correctly.